Principals' Managerial Skills in Improving Teacher Performance and Educational Quality in Public Elementary Schools in Cluster 6 of Kota Bahagia - Marwiyah Marwiyah; Bansu Irianto Ansari; Zahraini Zahraini (FKIP - Universitas Riau, 2026)
This study examined the principal’s managerial competence in improving teacher performance and educational quality at public elementary schools in Cluster 6 of Kota Bahagia District, South Aceh. The research focused on managerial functions including planning, organizing, directing, and supervision implemented by school principals in managing educational activities. A qualitative approach with a case study design was employed in this study. The participants consisted of 24 respondents, including 8 principals and 16 teachers and administrative staff. Data were collected through interviews, observations, questionnaires, and documentation. Data analysis used descriptive qualitative analysis based on the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings revealed that principals had implemented managerial functions relatively well through the preparation of School Work Plans (RKS) and School Activity and Budget Plans (RKAS), task distribution based on teacher competence, academic supervision, and continuous instructional guidance. Teacher involvement in planning and school management strengthened coordination and supported instructional effectiveness. Supervision and professional coaching conducted periodically contributed to improving teacher discipline, instructional responsibility, and classroom learning quality. Principals’ managerial competence therefore played an important role in improving teacher performance and educational quality within rural elementary school contexts.